Antimicrobial Resistance and Molecular Epidemiology of ESBL-Producing Escherichia coli Isolated from Outpatients in Town Hospitals of Shandong Province, China - Miao, Zengmin; Li, Song; Wang, Lei; Song, Wengang; Zhou, Yufa (Frontiers in Microbiology, 2017)
This study aimed to investigate antimicrobial resistance and molecular epidemiology of extended-spectrum β-lactamase (ESBL)-producing Escherichia coli (E. coli) isolated from outpatients in town hospitals of Shandong province, China. Antimicrobial susceptibility of ESBL-producing E. coli was tested using the disk diffusion and resistance genes encoding for β-lactamases (blaTEM, blaCTXM, and blaSHV) were detected by polymerase chain reaction (PCR). Multilocus sequence typing (ST) of ESBL-producing E. coli was analyzed in this study. Our results showed that of 320 E. coli isolates, 201 carried ESBL genes (201/320, 62.8％), and these isolates all carried blaCTX-M genes, the most common being blaCTX-M-14 (116/201, 57.7％), followed by blaCTX-M-55 (47/201, 23.4％) and blaCTX-M-15 (31/201, 15.4％). ESBL-producing E. coli exhibited highly resistant to penicillin derivatives, fluoroquinolones, folate pathway inhibitors, and third-generation cephalosporins, but no carbapenem-resistant isolates were found in this study. Forty-two STs were found among the 201 ESBL-producing E. coli, and the most common ST was ST131 (27/201, 13.4％), followed by ST405 (19/201, 9.5％) and ST69 (15/201, 7.5％). Taken together, a high isolation rate of ESBL-producing E. coli (62.8％) was found among outpatients in town hospitals. blaCTX-M gene was most dominant and was composed of a variety of subtypes. No dominant ST was detected among ESBL-producing E. coli, indicating that these ESBL-producing E. coli isolates derive from different clones.